Determinant factors for mortality of patients receiving mechanical ventilation and effects of a protocol muscle training in weaning. - Shimizu, Juliana Mitiko; Manzano, Roberta Munhoz; Quitério, Robison José; Alegria, Valdirene Tenório da Costa; Junqueira, Telma Tortorelli; El-Fakhouri, Silene; Ambrozin, Alexandre Ricardo Pepe (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Prognostic factors are used in the Intensive Care Unit (ICU) to predict morbidity and mortality, especially in patients on mechanical ventilation (MV). Training protocols are used in MV patients with the aim of promoting the success of the weaning process. Objective: To assess which variables determine the outcome of patients undergoing mechanical ventilation and compare the effects of two protocols for weaning. Method: Patients under MV for more than 48 hours had collected the following information: gender, age, ideal weight, height, Acute Physiology and Chronic Health Evaluation (APACHE II), risk of mortality, Glasgow Coma Scale (GCS) and index Quick and perfunctory (IRRS) breathing. Patients with unsuccessful weaning performed one of weaning protocols: Progressive T - tube or tube - T + Threshold ® IMT. Patients were compared for outcome (death or non-death in the ICU) and the protocols through the t test or Mann-Whitney test was considered significant when P <0.05. Results: Of 128 patients evaluated 56.25% were men, the mean age was 60.05 ± 17.85 years and 40.62% patients died, and they had higher APACHE II scores, mortality risk, time VM and IRRS GCS and the lower value (p<0.05). The age, initial and final maximal inspiratory pressure, time of weaning and duration of MV was similar between protocols. Conclusion: The study suggests that the GCS, APACHE II risk of mortality, length of MV and IRRS variables determined the evolution of MV patients in this sample. Not found differences in the variables studied when comparing the two methods of weaning.